2020
DOI: 10.5505/ejm.2020.80948
|View full text |Cite
|
Sign up to set email alerts
|

Use of Contractubex® (Allantoin, Heparin, Extractum Cepae) to Prevent Scar Formation in The Rabbits to Which Primary Closure has been Applied After Urethrotomy

Abstract: The scar tissue occurring in operating area after the repair of hypospadias which is one of the common congenital anomalies of male children has part in formation of post-operative complications. Many surgical techniques and materials have been used to reduce complications. The purpose of this study is to research the effects of contractubex ® (allantoin, heparin, extractum cepae [AHEC]) gel on development of scar in the area repaired after urethrotomy. In the study, 45 male White New Zealand rabbits were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In our study, it was observed that fibrosis developed less in the drug group than in the control group. Ayengin and Kilic [ 28 ] showed that contractubex reduced the development of fibrosis in their experimental hypospadias model, but the inflammation detected histopathologically was higher than the control.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was observed that fibrosis developed less in the drug group than in the control group. Ayengin and Kilic [ 28 ] showed that contractubex reduced the development of fibrosis in their experimental hypospadias model, but the inflammation detected histopathologically was higher than the control.…”
Section: Discussionmentioning
confidence: 99%